Diagnosis of intrachromosomal amplification of chromosome 21 (iAMP21) by molecular cytogenetics in pediatric acute lymphoblastic leukemia. Issue 10 (26th August 2015) - Duployez, Nicolas; Boudry‐Labis, Elise; Decool, Gauthier; Grzych, Guillaume; Grardel, Nathalie; Abou Chahla, Wadih; Preudhomme, Claude; Roche‐Lestienne, Catherine
Key Clinical Message Intrachromosomal amplification of chromosome 21 (iAMP21) defines a distinct cytogenetic subgroup of B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL) with poor prognosis that should be investigated in routine practice. Single‐nucleotide polymorphism (SNP)‐array provides a useful method to detect such cases showing a highly characteristic profile.